Descriptors controlling the catalytic activity of metallic surfaces toward water splitting - Jose L C Fajin (2010)
Periodic density functional theory (DFT) calculations have been used to unravel the existence of Bronsted-Evans-Polanyi (BEP) relationships for water dissociation on metallic surfaces which constitutes the rate determining step for the technologically important water gas shift reaction In addition it is predicted that nickel surfaces possessing low coordinated atoms could be effective for catalyzing water dissociation Finally it is shown that the adsorption energy of atomic oxygen on a given metallic surface provides an excellent descriptor of the activation energy for water dissociation on that surface thus allowing the screening of large number of metallic and bimetallic systems in a simple way